Effects of Sucrose and Plant Hormone on the Pigmentation of Mesocarp of White- and Red-Fleshed Peach Fruits - Inna Martha Rumainum; Kanjana Worarad; Yoshikazu Yamaki; Kenji Yamane (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Three cultivars of peach (Prunuspersica L. Batsch): ‘Ikeda’, ‘Akatsuki’ (white-fleshed) and ‘Tenshin Suimitsuto’ (red-fleshed) were used to study the effect of sucrose and auxin on the pigmentation of mesocarp. In the first experiment, mesocarp discs of ‘Ikeda’ and ‘Tenshin Suimitsuto’ were incubated on solidified MS medium containing sucrose, 1-naphtalene acetic acid (NAA), and their combination. A treatment of 10μM NAA increased the total of anthocyanin content in ‘Ikeda’. In ‘Tenshin Suimitsuto’, a treatment of 100 mM sucrose increased the total of anthocyanin content. In the second experiment, mesocarp discs of ‘Akatsuki’ and ‘Tenshin Suimitsuto’ were employed to examine the effect of 2,3,5-triiodobenzoic acetic acid (TIBA). The mesocarp discs were incubated on solidified MS medium containing NAA or combination of NAA and TIBA. A single TIBA treatment was applied in ‘Tenshin Suimitsuto’. TIBA treatment significantly (P<0.05) reduced the total anthocyanin content in both cultivars. The total phenolic content was decreased by TIBA treatment in both cultivars. A treatment of single TIBA (200 mM) significantly (P<0.05) inhibited anthocyanin, flavonoid and phenolic accumulation in ‘Tenshin Suimitsuto’. Present study shows that sucrose and auxin might regulate anthocyanin synthesis, as well as phenolic compounds, in the flesh of peach fruit.